The cytotoxic activity of pine needles ethanolic extract of Pinus merkusii on HeLa cell lines - Proboningrat, Annise; Fadholly, Amaq; Agus Sudjarwo, Sri; Abdul Rantam, Fedik; Budianto Achmad, Agung (BIO web of conferences, 2021)
Several efforts have been made to discover new anticancer agents based on natural ingredients. Meanwhile, previous studies have shown that different Pine genus species exhibit cytotoxic activity against various types of cancer cells. This plant is rich in phenolic compounds, especially procyanidins, flavonoids, and phenolic acids. Therefore, this study aims to investigate the in vitro cytotoxicity of Pinus merkusii needles extract on HeLa cancer cell lines. The cytotoxicity assessment was measured using MTT assay and expressed as IC 50 value. The results showed that the ethanolic extract poses a dose and time-dependent cytotoxic activity with an IC 50 value of 542.5 µg/ml at 48 hours of incubation. Based on this result, Pinus merkusii needles’ ethanolic extract has the potential of a novel candidate for an anticancer agent.